A primary understanding of field emission from superhigh specific surface area activated carbon with interconnection structure - Chen, Jiangtao (2022)
In this study, activated carbon (AC) with the specific surface area up to 3152 m2 g−1 is synthetized and structural-characterized. The AC powder displays the interconnective framework structure composed of numerous carbon nanosheets and the sharp edges act as the active sites to achieve efficient electron emission. The screen-printed AC cold cathode shows large emission current density of 15 mA cm−2 under relatively low electrical field of 6.0 V μm−1, with stable emission of up to 280 min. In conjunction to its uniform emission pattern, robustness, and vacuum-compatibility test, the feasibility of AC cold cathode in field emission devices have been demonstrated. This work provides a primary understanding of field emission performance for the AC electron emitter and expands the application fields of superhigh specific surface area AC.